PENINGKATAN RASA INGIN TAHU DAN HASIL BELAJAR MENGGUNAKAN MODEL PJBL BERBANTUAN MEDIA TTS SISWA KELAS V SD - Mia Okta Piani; Agnes Herlina Dwi Hadiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is a Classroom Action Research (PTK) using the PjBL model assisted by TTS media to increase the curiosity and learning outcomes of fifth grade students. The subjects of this study were fifth grade students of SD Kanisius Demangan Baru 1 in the 2023/2024 school year. For data collection techniques obtained by observation, questionnaires, interviews and tests. The data analysis technique used in this research is quantitative and qualitative data analysis. The results showed that the PjBL model assisted by TTS media could increase curiosity and learning outcomes. The average value of curiosity from the initial condition of 46.73 (low) in cycle 1 increased to 64.52 (Moderate), in cycle 2 increased to 79.72 (high). The average value of student learning outcomes from the initial condition value of 55.39 in cycle 1 increased to 76.08, in cycle 2 there was an increase to 88.26.